ANALISIS PENGARUH KUALITAS PRODUK, HARGA DAN IKLAN TERHADAP KEPUASAN PEMBELIAN PADA PT. ASKOTAMA INTI NUSANTARA - Bambang Ermansyah Saragih (Sekolah Tinggi Manajemen IMMI Jakarta, 2021)
The development of the business world in Indonesia iscurrently growing rapidly, considering that it has entered the era of globalization so that the business world isrequired to develop rapidly. Consumers prioritize product quality, affordable prices and the company's advertisementsare not excessive. Creating purchase satisfaction is a challenge for entrepreneurs because a buyer is now increasinglycritical in choosing the type of product and must match his expectations. The purpose of this study is to determine:Analysis of the Effect of Product Quality, Price and Advertising on Purchase Satisfaction at PT. Askotama IntiNusantara.“The sampling technique used in this study the author uses the Random Sampling technique (Randomlyon All Consumers) where each member of the population has the same opportunity to be selected as the overallsample, but the sample in this study is the entire population that is sampled .“The results obtained that partially andsimultaneously there is a positive and significant influence between Product Quality, Price, Advertising on Purchase Satisfaction.